Flexibility without security: Labour market integration mechanisms in Hungary during the 2010s - Illéssy, Miklós; Huszár, Ákos; Csizmadia, Péter (Intersections. East European Journal of Society and Politics, 2024)
The paper aims to summarise the role of social integration in the labour market processes of the 2010s in Hungary. We have left behind a key decade when employment growth reached unprecedented proportions. However, this unprecedented growth had serious social costs, as those excluded from the labour market during the break-up of the welfare state were left without social protection, and because the financial situation of those entering the labour market improved in absolute terms. Still, their relative deprivation did not change or worsened, and in the meanwhile their ability to enforce their interests has been significantly reduced. That is, today’s Hungarian government wants to integrate the members of society into the labour market. To this end, it provides increasingly weak protection for those who, due to old age, long-term illness or unemployment, are forced to stay out of the labour market. Disintegration affects those with the fewest resources, the least capable of conflict and those unable to articulate their problems in public most: these are women, young people and older workers who are ‘traditionally’ in a worse position in the labour market, in addition to those who are forced out of the labour market. The question is whether the current social model or the situation of those who disintegrated from the labour market will continue to deteriorate after the economic slowdown.